Linking renewables and fossil fuels with carbon capture via energy storage for a sustainable energy future - Hanak, Dawid P.; Manovic, Vasilije (Springer Science Business Media, 2019)
Renewable energy sources and low-carbon power generation systems with carbon capture and storage (CCS) are expected to be key contributors towards the decarbonisation of the energy sector and to ensure sustainable energy supply in the future. However, the variable nature of wind and solar power generation systems may affect the operation of the electricity system grid. Deployment of energy storage is expected to increase grid stability and renewable energy utilisation. The power sector of the future, therefore, needs to seek a synergy between renewable energy sources and low-carbon fossil fuel power generation. This can be achieved via wide deployment of CCS linked with energy storage. Interestingly, recent progress in both the CCS and energy storage fields reveals that technologies such as calcium looping are technically viable and promising options in both cases. Novel integrated systems can be achieved by integrating these applications into CCS with inherent energy storage capacity, as well as linking other CCS technologies with renewable energy sources via energy storage technologies, which will maximise the profit from electricity production, mitigate efficiency and economic penalties related to CCS, and improve renewable energy utilisation.
Keywords: carbon capture; energy storage; renewable energy sources; decarbonisation; fossil fuels